Face and content validation of the amyotrophic lateral sclerosis—Bulbar dysfunction index (ALS-BDI) - Yunusova, Yana; Waito, Ashley; Barnett Tapia, Carolina; Huynh, Anna; Martino, Rosemary; Abrahao, Agessandro; Pattee, Gary L.; Berry, James D.; Zinman, Lorne; Green, Jordan R. (Frontiers in Neurology, 2023)
Early detection and tracking of bulbar dysfunction in amyotrophic lateral sclerosis (ALS) are critical for directing management of the disease. Existing physiological assessments of bulbar dysfunction are often inaccessible and cost-prohibitive for clinical application. Existing clinical assessments are limited. The overall goal of our research is to develop a brief and reliable, clinician-administered assessment tool, the ALS Bulbar Dysfunction Index (ALS-BDI) to evaluate bulbar dysfunction. The aim of this study was to establish content and face validity of the ALS-BDI through item generation and reduction, including item scoring. Two drafts of the ALS-BDI were developed. The first draft contained 48 items, after a review of existing clinical tools for their relevance to bulbar dysfunction in ALS. Of the 48 items, 35 items were retained after surveying experts and clinician users for their relevance, feasibility, interpretability, and appropriateness. The second draft of the ALS-BDI contained 37 items, due to one item splitting, based on users cognitive interviews. The ALS-BDI described in this study aims to provide a brief and reliable, clinician-administered assessment tool to evaluate bulbar dysfunction in patients with ALS. Future research will evaluate the psychometric properties of this tool including its reliability, validity, and responsiveness to change over time.